Development of Teacher Communication Patterns and Parental Involvement Instrument: Validity and Reliability Testing - Febritesna Nuraini; Djoko Saryono; Abdul Latif; Intan Farnisyah; Azizah binti Zain; M.Ishaq; Bambang Sudarsono; Putri Sabrina Uswatun Hasanah (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2026)
Background of Study: Effective collaboration between teachers and parents is crucial in early childhood education. However, the absence of a standardized and psychometrically sound instrument to measure these dynamics in the Indonesian kindergarten context poses a challenge. Aims and Scope of Paper: This study aims to develop and validate a research instrument measuring teachers' two-way communication patterns and parental involvement. The novelty lies in its dual-construct design, rigorous psychometric validation, and contextual adaptation for Indonesian kindergartens. Methods: This development research employed a quantitative approach. The instrument consisted of two scales: Teacher Two-Way Communication (15 items) and Parental Involvement (31 items across six dimensions). The tool was tested on 150 parents of kindergarten students in Yogyakarta City. Item validity was analysed using Pearson Product-Moment correlation, and reliability was measured using Cronbach’s Alpha coefficient. Summary of Results or Findings: The findings indicate that all items in both scales were valid. The scales demonstrated very high reliability (Teacher Communication α = 0.92; Parental Involvement α = 0.88). Simple linear regression analysis revealed that teacher communication significantly influences parental involvement (R² = 0.462, p < 0.001). Conclusion: The study successfully produces a valid and reliable instrument and empirically confirms the critical role of teacher communication in fostering parental involvement. This tool is recommended for educators and researchers to facilitate better home-school collaboration.